MPower designing restorative open spaces in a manufacturing economic zone to support workers’ well-being - Manalo, Francis Kyle I.
One of the major factors contributing to the global health crisis is stress in which the workplace environment is identified as one of the possible causes of stress or avenues for restoration since studies suggest that the quality of the physical working environment can either improve or worsen the health and well-being of the workers depending on its supportiveness. Since exposure to the monotonous, lifeless, and standardized appearance of industrial areas has been identified as a contributing factor to the stress experienced by the workers, this study aims to highlight the significance of the outdoor environment in influencing the health and well-being of the industrial workers, by exploring the open spaces of an active industrial complex. Key findings from the study show that majority of the respondents are moderately stressed. The open spaces provide some level of support but there is still room for improvement to help alleviate stress. When assessed against employee preference, some gaps have been highlighted that need to be addressed accordingly. A general guideline which is primarily patterned after environmental theories about health and well-being (SRT, ART, SDT, Sustainable landscape design) and work-related concepts (Effort-recovery model and General Adaptation Syndrome) has been conceptualized which can be followed for other industrial areas. In brief, the results of this study suggest that the open spaces in industrial areas are currently not supportive enough to the well-being of the workers and can still be further improved with the prioritization on visual, noise, air pollution buffers, adaptive safe spaces, low to light-intensity activities and multi-sensory environments based on their needs and preferences.